Use of Video Learning Media with the Problem Based Learning (PBL) Learning Model to Improve Student Learning Outcomes at SMK Negeri 8 Tangerang Regency - Tuwandi Tuwandi (Journal of Social Research, 2023)
The objective of this research is to describe the application of the Problem Based Learning (PBL) model to improve the learning outcomes of class XI Office Management (MPK) 2 students at SMK Negeri 8 Kab. The data studied consisted of 26 students. In the first cycle, the researcher compiled and prepared a Learning Implementation Plan (AJAR MODULE) referring to the Merdeka curriculum by applying a scientific approach and using the discussion learning method in the second week of September 2023 with the subject Sequences and Series, chapter on Quadratic Equations and Functions. The researcher then continued with the instruction using the cooperative learning model with the Think Pair Share (TPS) type, covering the topic of number conversion in the computer system course for the odd semester of 2023/2024. The posttest activity was carried out by 26 female students in the third week of October 2023. The classical completeness rate of 84.6%, as seen from the posttest results, indicates that 22 students scored above 76, in line with the minimum passing standard set by the researcher in this classroom action research. Twenty-two students were able to achieve scores below 76 or above the KKM set.